Joint DFT and Spacetime Coding for MU-OFDM in Power-Constrained Optical Wireless Communication Systems - Dianbin Lian; Yan Gao; Jie Lian; Yong Li (Photonics)
The application of DFT precoding in mitigating peak-to-average power ratio (PAPR) issues in optical wireless communication systems under power constraints is well established. However, the channel spatial diversity for multiusers needs to be considered. This paper proposes a joint DFT and spacetime precoding technique to support multiple users and mitigate the PAPR for optical wireless communication systems when OFDM modulation is used. In our study, we introduce the weighted Bussgang theorem as an alternative method for evaluating the communication performance of hard-clipped systems due to the transmitted power constraint. Our numerical results demonstrate the effectiveness of this approach in analyzing SNR and BER performance.